Lipid metabolism in the adrenal gland - Aderhold, Anika; Alexaki, Vasileia Ismini (Frontiers in Endocrinology, 2025)
The adrenal gland consists of the medulla and the cortex. The chromaffin cells of the adrenal medulla release catecholamines via regulated exocytosis. Vesicle formation, trafficking, maturation and fusion with the plasma membrane are orchestrated by lipids such as cholesterol, diacylglycerol, phosphatidic acid and phosphatidylinositol-4,5-bisphosphate. On the other hand, the adrenal cortex is a highly specialized lipid-metabolizing organ secreting steroid hormones. Cholesterol, acquired from circulating lipoproteins and de novo biosynthesis, is mobilized from intracellular stores and transported to mitochondria to be used as a substrate for steroidogenesis. Steroidogenesis is regulated by free polyunsaturated fatty acids (PUFA) and an increased PUFA content in phospholipids promotes steroidogenesis. Cholesterol efflux and lipid-processing macrophages further contribute to lipid homeostasis in the adrenal gland. Given that lipidomics have revolutionized our perception of cell function, we anticipate that this will also hold true for the investigation of adrenocortical function. Such investigations may pinpoint novel targets for the management of abnormal adrenal function.